Origins of house reinfestation with Triatoma infestans after insecticide spraying in the Argentine Chaco using wing geometric morphometry - Gaspe, Maria Sol (2013)
Identifying the origins of insect vectors collected after community-wide residual insecticide applications is a relevant challenge in the Gran Chaco region where the main vector of Chagas disease Triatoma infestans usually reinfests human dwellings. Wing geometric morphometry was used to compare the right wings of 63 males and 54 females collected at 4. months post-spraying (MPS) with those from 165 males and 111 females collected before full-coverage spraying with pyrethroids in a well-defined rural area in Northeastern Argentina. Male and female wing centroid size resulted significantly larger at 4. MPS than before interventions, but no significant changes in shape were detected. Metric disparity (variance of shape) varied significantly in males but not in females. Using shape variables, a relatively large fraction of post-spraying males (70%) and females (54%) could not be differentiated from those collected at the same source house or at the nearest infested house before interventions. Bugs collected at 4 and 8. MPS in a persistently infested house were mainly assigned to the source house. These results support the hypothesis of persistent bug populations that survived the insecticide application at local spatial scales, and are consistent with the occurrence of vector control failures most likely related to moderate pyrethroid resistance. Wing geometric morphometry is a useful tool for identifying sources of reinfestation, but it is limited by the spatial structure found in the reference populations. Combined with field and genetic data, this approach may contribute to the understanding of the reinfestation process and improvement of vector control strategies.